Aircraft measurements of aerosol distribution, warm cloud microphysical properties, and their relationship over the Eastern Loess Plateau in China. Issue 1 (1st January 2019) - Li, Junxia; Li, Peiren; Ren, Gang; Yuan, Liang; Li, Yiyu; Yang, Junmei
Abstract: In situ aircraft measurements of aerosols and clouds were performed over the eastern Loess Plateau in Shanxi Province, China. The microphysical properties of both aerosols and warm clouds, including aerosol number concentration ( N a ), particle effective diameter (ED), number concentration of cloud droplets ( N c ), cloud droplet diameter ( D c ), and liquid water content (LWC) of clouds, determined through six flight observations performed in May 2013 were obtained and analysed. The mean magnitude of measured N a over the six flights was 10 3 cm −3, and accumulation mode particles dominated the majority. Most EDs of aerosol particles were less than 1 μm. Large amounts of fine aerosol particles were constrained to the lower layer, with ED smaller than 0.5 μm, and N a decreased with height. The base heights of warm clouds ranged from 1000 to 2800 m. The maximum and average values of the measured N c ranged from 147 to 311 cm −3 and 51 to 157 cm −3, respectively. The maximum and average D c ranged from 13.5 to 28.9 and 5.8 to 13.1 μm, respectively. The average LWC of warm clouds was 0.05 g·m −3 . N a was negatively correlated with N c either in the vertical or horizontal direction. N c was higher with a smaller size of cloud droplets under high aerosol loading conditions. A small number of cloud droplets with larger size were formed under low aerosol loading conditions. At a certain range of LWC, N c and D c showed a negative correlation. The increase in LWC was related to an increase in the size of cloud droplets rather than the number of cloud droplets. The cloud droplet size distribution showed that small droplets dominated the total cloud droplet concentration. A bimodal lognormal distribution function can be efficiently used to describe the average spectrum of warm cloud droplets.